Half‐Sandwich Guanidinate–Osmium(II) Complexes: Synthesis and Application in the Selective Dehydration of Aldoximes. Issue 3 (21st December 2015) - Francos, Javier; González‐Liste, Pedro J.; Menéndez‐Rodríguez, Lucía; Crochet, Pascale; Cadierno, Victorio; Borge, Javier; Antiñolo, Antonio; Fernández‐Galán, Rafael; Carrillo‐Hermosilla, Fernando
Abstract: The novel guanidinate–osmium(II) complexes [OsCl{κ 2 ‐( N, N′ )‐C(NR)(N i Pr)NH i Pr}(η 6 ‐ p ‐cymene)] [R = Ph (3a ), 4‐C6 H4 F (3b ), 4‐C6 H4 Cl (3c ), 4‐C6 H4 CF3 (3d ), 3‐C6 H4 CF3 (3e ), 3, 5‐C6 H3 (CF3 )2 (3f ), 4‐C6 H4 CN (3g ), 4‐C6 H4 Me (3h ), 3‐C6 H4 Me (3i ), 2‐C6 H4 Me (3j ), 4‐C6 H4 t Bu (3k ), 2, 6‐C6 H3 i Pr2 (3l ), 2, 4, 6‐C6 H2 Me3 (3m )] have been synthesized in high yields (70–88 %) by treatment of THF solutions of the dimeric precursor [{OsCl(µ‐Cl)(η 6 ‐ p ‐cymene)}2 ] (1 ) with 4 equivalents of the corresponding guanidine ( i PrHN)2 C=NR (2a–m ) at room temperature. The easily separable guanidinium chloride salts [( i PrHN)2 C(NHR)]Cl (4a–m ) were also formed in these reactions. The structures of3a, 3d, and3h were unequivocally confirmed by X‐ray diffraction methods. Complexes3a –m proved to be active in the catalytic dehydration of aldoximes. The best results were obtained with [OsCl{κ 2 ‐( N, N′ )‐C(N‐4‐C6 H4 CF3 )(N i Pr)NH i Pr}(η 6 ‐ p ‐cymene)] (3d ; 5 mol‐%), which, in acetonitrile at 80 °C, was able to convert selectively a large variety of aromatic, heteroaromatic, α, β‐unsaturated, and aliphatic aldoximes into the corresponding nitriles in high yields and short reaction times. Abstract : Novel osmium(II)–guanidinate complexes of general composition [OsCl{κ 2 ‐( N, N′ )‐C(NR)(N i Pr)NH i Pr}(η 6 ‐ p ‐cymene)] (R = Ar) have been synthesized and successfully employed as catalysts for the selective conversion of aldoximes into nitriles.